Tourism Waste Management Governance in Denpasar City After the Closure of Suwung Landfill - I Wayan Suwitantra; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract Denpasar City functions as an urban center and a major support area for Bali’s tourism sector, facing significant pressure in waste management. According to the National Waste Management Information System (SIPSN), Bali generates approximately 1.2 million tons of waste annually, with Denpasar City identified as the largest contributor at the provincial level. Waste composition is dominated by organic waste at around 68%, while plastic waste remains a critical issue in urban and tourism areas. During peak events, such as New Year’s Eve, Denpasar’s Environmental Agency recorded a surge of 900–1,000 tons of waste collected within a single day. The waste management challenge has become more critical following the overcapacity condition and planned permanent closure of the Suwung landfill, which has long served as the primary final disposal site for the Sarbagita region, with a transition period extending to 2026. This situation requires a fundamental transformation of urban and tourism waste management systems in Denpasar. This study aims to analyze the governance of tourism waste management in Denpasar City after the closure of the Suwung landfill using a qualitative descriptive approach through policy analysis, secondary data review, and examination of official government documents. The findings indicate that the main challenges include high waste generation rates, limited decentralized waste processing infrastructure, suboptimal waste segregation at the source, and weak integration of the tourism sector into the urban waste management system. In conclusion, strengthening collaborative governance involving local government, tourism actors, and communities is essential to improve tourism waste management in Denpasar City. Enhancing public service capacity, enforcing regulatory frameworks, and promoting waste reduction at the source are key to ensuring environmental sustainability and maintaining Bali’s tourism competitiveness. Keywords: Denpasar City, Environmental Sustainability, Public Governance Tourism, Waste Management.